Impact of Empowering Leadership on Antimicrobial Stewardship: A Single Center Study in a Neonatal and Pediatric Intensive Care Unit and a Literature Review - Steinmann, Karin E.; Lehnick, Dirk; Buettcher, Michael; Schwendener-Scholl, Katharina; Daetwyler, Karin; Fontana, Matteo; Morgillo, Davide; Ganassi, Katja; O'Neill, Kathrin; Genet, Petra; Burth, Susanne; Savoia, Patrizia; et al. (Frontiers in Pediatrics, 2018)
Background Antimicrobial stewardship (AMS) is an important strategy of quality improvement for every hospital. Leadership is an important factor for implementation of quality improvement and AMS programs. Recent publications show successful AMS programs in children’s hospitals, but successful implementation is often difficult to achieve and literature of AMS in neonatal and pediatric intensive care units (NICU/PICU) is scarce. Lack of resources and prescriber opposition are reported barriers. A leadership style focusing on empowering frontline staff to take responsibility is one approach to implement changes in health care institutions. Aim Systematic literature review regarding empowering leadership and AMS in health care and assessment of the impact of such a leadership style on AMS in a NICU/PICU over three years. Methods Assessment of the impact of a leadership change September 1, 2015 from control-driven to an empowering leadership style on antibiotic use and hospital acquired infections. Prospective analysis and annual comparison of antibiotic use, rate of suspected and confirmed ventilator-associated pneumonia (VAP) and central-line associated blood stream infection (CLABSI) including antibiotic use overall, antibiotic therapy for culture-negative and culture-proven infections including correct initial choice and streamlining of antibiotics in the NICU/PICU of the Children’s Hospital of Lucerne between January 1, 2015 and December 31, 2017. Results Five articles were included in the literature review. All five studies concluded that an empowering leadership style may lead to a higher engagement of physicians. Three out of five studies reported improved AMS as reduced rate in hospital-acquired infections and improved prevention of MRSA infections. From 2015 to 2017, antibiotic days overall and antibiotic days for culture-negative situations (suspected infections and prophylaxis) per 1000 patient days declined significantly from 474.1 to 403.9 and from 418.2 to 309.4 days, respectively. Similar, the use of meropenem and vancomycin declined significantly. Over the three years, suspected and proven VAP- and CLABSI-episodes decreased with no confirmed episodes in 2017. Conclusion An empowering leadership style which focuses on enabling front line physicians to take direct responsibilities for their patients may be a successful strategy of antimicrobial stewardship allowing to overcome reported barriers of AMS implementation.